Crystal structures of DCAF1-PROTAC-WDR5 ternary complexes provide insight into DCAF1 substrate specificity - Mark F. Mabanglo; Brian Wilson; Mahmoud Noureldin; Serah W. Kimani; Ahmed Mamai; Chiara Krausser; Héctor González-Álvarez; Smriti Srivastava; Mohammed Mohammed; Laurent Hoffer; Manuel Chan; Jamie Avrumutsoae; et al. (Nature Communications)
Abstract Proteolysis-targeting chimeras (PROTACs) have been explored for the degradation of drug targets for more than two decades. However, only a handful of E3 ligase substrate receptors have been efficiently used. Downregulation and mutation of these receptors would reduce the effectiveness of such PROTACs. We recently developed potent ligands for DCAF1, a substrate receptor of EDVP and CUL4 E3 ligases. Here, we focus on DCAF1 toward the development of PROTACs for WDR5, a drug target in various cancers. We report four DCAF1-based PROTACs with endogenous and exogenous WDR5 degradation effects and high-resolution crystal structures of the ternary complexes of DCAF1-PROTAC-WDR5. The structures reveal detailed insights into the interaction of DCAF1 with various WDR5-PROTACs, indicating a significant role of DCAF1 loops in providing needed surface plasticity, and reflecting the mechanism by which DCAF1 functions as a substrate receptor for E3 ligases with diverse sets of substrates.